The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.yexmp.2011.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in the brains of young patients with poorly controlled T1DM and fatal diabetic ketoacidosis

Abstract: Semi-quantitative neuroradiologic studies, quantitative neuron density studies and immunocytochemistry markers of oxidative stress and neuroinflammation indicate neuronal injury and deficits in young patients with chronic poorly controlled type 1 diabetes mellitus (T1DM). Present data suggest that pathogenesis of the neuronal deficits in young patients, who die as the result of diabetic ketoacidosis (DKA) and brain edema (BE), does not involve apoptosis, a prominent form of regulated cell death in many disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 114 publications
3
14
0
Order By: Relevance
“…This speculation is consistent with a recent report demonstrating a 3-4-fold increase autophagosomes in the brain neurons of mice fasted for 48 h [88,89]. Moreover, macroautophagy is markedly up-regulated in the brains of type 1 diabetics who have died of ketoacidosis [90].…”
Section: Autophagy May Mediate Some Neuroprotective Benefits Of Ketogsupporting
confidence: 93%
“…This speculation is consistent with a recent report demonstrating a 3-4-fold increase autophagosomes in the brain neurons of mice fasted for 48 h [88,89]. Moreover, macroautophagy is markedly up-regulated in the brains of type 1 diabetics who have died of ketoacidosis [90].…”
Section: Autophagy May Mediate Some Neuroprotective Benefits Of Ketogsupporting
confidence: 93%
“…Previous studies have demonstrated that the ketones, especially AA, can generate superoxide radicals and induce cytokine and adhesion molecule expression, and that ketonemic diabetics have high levels of oxidative stress compared to those of normoketonemic diabetic patients [13,14,16,20,24,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54]. We observed that AA was significantly able to upregulate NOX4 expression and NADPH oxidase activity, while BHB failed to produce any adverse effects in HUVEC.…”
Section: Discussionmentioning
confidence: 99%
“…The autophagy pathway is sensitive to alterations in glucose metabolism (Figure 3). In the brain, young patients with poorly controlled Type I diabetes exhibit increased autophagy protein LC3 and Atg4, increased ER-associated glucose-regulated protein78/binding immunoglobulin protein (GRP78/BiP) [70]. In stroke and cerebral ischemia, oxygen and glucose deprivation occurs.…”
Section: Glucose Metabolism and Autophagymentioning
confidence: 99%